2016
DOI: 10.1007/s00122-016-2779-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rhg1 copy number, type, and interaction with Rhg4 on resistance to Heterodera glycines in soybean

Abstract: Evaluations of soybean populations showed that both Rhg1 copy number and type were important in determining soybean cyst nematode resistance with higher copy number within Rhg1 type conferring greater resistance. Rhg1 and Rhg4 are important loci conferring resistance to soybean cyst nematode (SCN; Heterodera glycines). Alleles at Rhg1 have been shown to vary for copy number and type and the importance of this variation in conferring resistance is not well defined. The repeat number ranges from one to 10 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Although rhg1-a seems to confer some amount of resistance in the cv Forrest GmSHMT08 null mutant, the contribution from other minor quantitative trait loci cannot be ignored . Yu et al (2016) showed that rhg1-a alone may confer some level of resistance in crosses using PI 437654, a PI with a similar copy number (three copies) to that in cv Forrest. PI 437654 has a similar epistatic relationship between rhg1 and Rhg4 in conferring resistance to SCN (Wu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although rhg1-a seems to confer some amount of resistance in the cv Forrest GmSHMT08 null mutant, the contribution from other minor quantitative trait loci cannot be ignored . Yu et al (2016) showed that rhg1-a alone may confer some level of resistance in crosses using PI 437654, a PI with a similar copy number (three copies) to that in cv Forrest. PI 437654 has a similar epistatic relationship between rhg1 and Rhg4 in conferring resistance to SCN (Wu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of the proportion of alternatively spliced α-SNAP Rhg1 LC transcript could provide a bypass that reduces disruptive α-SNAP production and promotes balance with regard to wild-type α-SNAPs. Other areas for future work are suggested by the positive correlation between the strength of SCN resistance and copy number of high-copy (α-SNAP Rhg1 HCencoding) Rhg1 repeats (9,21,47,48). Improved SCN resistance may be obtained if haplotypes can be identified or generated that carry more Rhg1 copies than the current mainstay 10-copy haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…Epistasis between the rhg1 and Rhg4 has been studied in the past two decades (Brucker et al, 2005;Meksem et al, 2001). Recently, Yu et al (2016) reported the advantage of the 'Peking'-type (an Rhg4 required resistance) over the 'Fayette' (PI88788 type of resistance) and described the presence of a greatest resistance to two Hg-types tested; Hg type 2.5.7 and Hg type 7, pointing to the rhg1 copy number and type as important in determining the SCN resistance. In the previous study, the impact of the Rhg4 on high copy rhg1 soybean lines (PI88788 type) was not observed, suggesting that the difference between the rhg1 sequences of 'Peking' and 'Fayette' might be the key to understanding the interaction between these alleles.…”
Section: Epistatic Interactions Between the Rhg1 And Rhg4 Locimentioning
confidence: 99%